Non-finite-based remote past in Udmurt: Resultative and experiential functions - Saraheimo, Mari (Finnisch-Ugrische Forschungen, 2024)
The article deals with three constructions in Udmurt based on the past participle, combined with the past tense copula (valPST1/vi̮lemPST2). The aim of the study is to describe the functions of the following constructions: 1) the experiential construction + val/vi̮lem, 2) the resultative construction + val/vi̮lem and 3) the past participle + val/vi̮lem. These constructions are examined through the theory of perfects and pluperfects and whether the constructions carry out functions typical of those of a (plu)perfect. The results of the study show that the constructions in question carry out functions typical of pluperfects, such as past relevance perfect, past experiential and counterfactual functions. The construction formed with the past participle is found to be evidentially neutral and by and large corresponding to the first finite remote past, albeit declining in use and stylistically nuanced. The so-called resultative construction, on the other hand, may acquire various meanings depending on the semantics of the verb, among them past resultative action, past relevance perfect, and past continuative. Contrary to previous descriptions, the resultative construction may also occur with an external subject argument. Finally, the constructions also carry out similar discourse-pragmatic functions as their finite counterparts, such as attenuating questions, expressing assertivity, mirativity, and marking a pre-mirative context.